O Ensino de Ciências e a conservação dos recursos hídricos: uma proposta metodológica usando um espaço não formal - Santos, Adriana Araújo Pompeu Piza (2010)
The hydro resources in the planet are ever more scarcity. Despite of the Amazon process 14% of the freshwater in the planet already demonstrate problems related with the hydro resources conservation. The our work is linked with the actual emergency of hydro resources conservation and the missing of new methodologies, which could really contribute to the empowerment of Science Teaching. In this sense this work avalue the problem of teaching onto hydro resources conservation and the use of non-formal classes as methodology of this teaching-learning process. The research was carried out at North Zone School in Manaus, Amazonas. With the purpose of to indagate as occurs the teaching onto hydro resources, the working books of Science and Geography adopted by the school and Brazilian Curricular Parameters of Natural Science were evaluated. In addition to this, a science and geography class at four rooms of 6th year Fundamental Class were checked to carry out observations, and was applied questionnaire to four teachers and 115 students. The Lagoon Carbrás was chose as non-formal space to rollout this work. To purpose about the Lagoon historical were interviewed twenty neighboards. Since of the data analyses were possible spot the information failure from the students about water subject. Due to this situation, after a class at non-formal space – the Lagoon Carbrás, followed a speech of hydro resources, and experiences and games. To complete this work aiming to realize in which manner that the methodology used added value, the same questionnaire was applied again. In the questionnaire applied the wrong answers were dropped 127%, the in blank questions reduced 850% and the right answers were 100% better. The analyses of working books to show a nonrelated and little realist vision about hydro resources in the local and regional level. The scarcity vision of hydro resources in our Amazon Region is very difficult to understand from the students. The methodology used to set up this knowledge provider of reflection and matched attitude with the actual emergency of hydro resources. This work give us a chance to produce a Science Teaching learning proposal called dive deeper, in which the water subject are rolled out based on Amazon Region perspective.